Exploring the Verdict of Interfaith Marriage under Maqāṣid Sharīa Insights - Bukido, Rosdalina; Ishak, A. Zainal Azhar (Mazahibuna: Jurnal Perbandingan Mazhab, 2024)
The diverse society of Indonesia permits interfaith marriage but the challenge lies in the legal recognition under Islamic law. The primary issue pertains to the legal aspects and the jurisprudence from the perspective of Maqāṣid Sharīa. Therefore, this research aimed to analyze the legal objectives of interfaith marriage as well as the execution and status of the concept from the perspective of Maqāṣid Sharīa. A thorough examination of literature from primary, secondary, and tertiary sources is carried out, including legislation, court judgments, books, journals, and other relevant materials. Meanwhile, the analysis is performed using a juridical, syar'i, and philosophical perspective. The results show that the judge approved the application for the legality of interfaith marriage, citing Law Number 1 of 1974 on Marriage, Human Rights, and Law Number 23 of 2006 on Population Administration. Similarly, when considering Maqāṣid Sharīa, marriage between individuals of different religions is not allowed, particularly in matters of Aqidah and Iman. This prohibition upholds the objectives of Islamic marriage law since the values obtained from the religion are not easily reconciled in the unions. According to the principles of Maqāṣid Sharīa, interfaith marriage should be avoided due to potential harm.